How to Build Collective Capabilities: The 3C-Model for Grassroots-Led Development. Issue 2 (3rd April 2017) - Ibrahim, Solava
Abstract: Capabilities need to be built from the bottom-up. Social innovations at the grassroots seek to present new solutions to existing social problems. However, since the poor suffer from limitations on their individual capabilities and agency, they engage in acts of collective agency to generate new collective capabilities that each individual alone would not be able to achieve. The question is: how can these acts of collective agency be initiated, supported and sustained in practice? What roles can development actors (such as the state, donors and NGOs) play in supporting these acts of collective agency? Drawing on the literature on social innovation, the capability approach, participation and empowerment, the paper argues that three crucial C-processes are integral conditions for promoting successful, scalable and sustainable social innovations at the grassroots, namely: (1)C onscientization; (2)C onciliation and (3)C ollaboration. By linking the individual, collective and institutional levels of analysis, the paper demonstrates the importance of individual behavioural changes, collective agency and local institutional reforms for the success, sustainability and scalability of social innovations at the grassroots. The paper acknowledges conflict, capture and cooptation as potential limitations and recognizes the role of contextual factors in initiating, implementing and sustaining social innovations at the grassroots.